Star‐Shaped Gold Nanoparticles as Friendly Interfaces for Protein Electrochemistry: the Case Study of Cytochrome c. Issue 17 (11th September 2019) - Silveira, Célia M.; Zumpano, Rosaceleste; Moreira, Miguel; de Almeida, Miguel Peixoto; Oliveira, Maria João; Bento, Marina; Montez, Cláudia; Paixão, Inês; Franco, Ricardo; Pereira, Eulália; Almeida, M. Gabriela
Abstract: Gold nanostars with an average tip‐to‐tip length of 52±6 nm were functionalized with different capping agents and used as electrode modification materials for protein electrochemistry. Direct electron transfer between cytochrome c and nanostar‐coated pyrolytic graphite electrodes was observed with the protein in solution. The electrochemical response was improved at nanostars functionalized with a 1 : 1 mixture of 11‐mercaptoundecanoic acid and 4‐mercaptobenzoic acid in comparison with gold nanospheres coated with a similar functionalization. Further immobilization of cytochrome c on pyrolytic graphite while conjugated with the same nanostars guaranteed the maintenance of the protein's native properties, whereas direct adsorption on the bare or nanostar‐modified electrodes resulted in an altered conformational state. The pseudo‐peroxidase activity of the altered cytochrome c was enhanced in the presence of the nanostars. Abstract : Wish upon a star : The direct electron transfer reaction of cytochrome c (cyt c ) is evaluated at pyrolytic graphite electrodes modified with gold nanostars functionalized with different capping agents. The diffusion‐controlled electrochemistry of cyt c is investigated, as well as its behavior upon adsorption to the modified electrode or when electrostatically coupled to the gold nanostars, forming bionanoconjugates.